Lactulose - Vera-Vera, C (Springer International Publishing, 2023)
Lactulose is a synthetic disaccharide with various applications in the pharmaceutical, food, and feed sectors. Being a prebiotic, its consumption provides several health benefits to the consumer. Lactulose has been used in the clinical treatment of constipation for over 50 years and is registered as a pharmaceutical drug in more than 100 countries. More recently it is being used as a functional ingredient in foods. Lactulose is industrially produced by the alkaline isomerization of lactose; however, this route produces undesirable and hard-to-remove side products, so that lactulose purification demands several complex downstream operations. The biocatalytic route to lactulose appears as a more sustainable technology in line with the principles of green chemistry and circular economy. Lactulose can be produced enzymatically either by the transgalactosylation of fructose with lactose, catalyzed by B-galactosidases or, by the direct isomerization of lactose, catalyzed by cellobiose 2-epimerases, both routes having their pros and cons. This chapter presents an in-depth updated revision of the different strategies for lactulose synthesis, analyzing the impact of biocatalyst, reaction medium, and reactor engineering on lactulose yield and productivity. Functional properties and industrial production of lactulose are also reviewed. © Springer Nature Switzerland AG 2023.